(untitled) (International Journal of Educational Management, Rivers State University., 2025)
The study examined influence of school-community relationships on sustainable school administration in Public Senior Secondary Schools in Abua/Odual LGA, Rivers State. Three research questions and three hypotheses guided the study. The study adopted descriptive survey design. The total population was 2793 respondents consisting of 2,760 Parent Teachers Association (PTA) members and 33 principals from 11 public senior secondary schools in Abua/Odual Local Government Area of Rivers State. A sample size of 350 respondents comprising of 317 Parent Teachers Association and 33 principals was derived through Taro Yamane’s formula and simple random sampling technique. The instrument was a self-developed questionnaire titled: Influence of School Community Relationships on Sustainable School Administration Questionnaire” which was face and content validated by experts in Measurement and Evaluation and Department of Educational Management, all in Rivers State University. Cronbach Alpha statistics was used for the reliability of the instrument which yielded reliability indexes of 0.72, 0.80 and 0.85 respectively. Mean and standard deviation were used to answer the research questions while z-test was used in testing the formulated null hypotheses at 0.05 level of significance. Findings of the study revealed that to a very high extent school modern, school alienative and cooperative relationships influences sustainable school administration in public senior secondary schools in Abua/Odual Local Government Area of Rivers State. Based on the findings, it was recommended among others that School principals should create a more robust relationship with the community and the community should in return reciprocate in enhancing the relations.